Cement replacement in pervious concrete: feasibility of using sugar cane ashes and sand considering the overall performance of the material - Silva, Rodrigo Garozi da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Pervious concrete (PC) is a material with interconnected macropores (approximately 15-35% porosity) that allows water to drain through its structure, generally used in pervious pavements. It is made with coarse aggregates bonded by a cementitious paste, and generally with little or no incorporation of fine aggregate, which guarantees interconnected porosity. Due to the absence of fines and high porosity, this material may require a greater amount of cement and achieves lower mechanical performances than conventional concrete. Considering the environmental and cost issues associated with the production of Portland cement, this work focused on the use of supplementary cementitious materials and fine aggregate replacing Portland cement in pervious concretes. Sugar cane bagasse ash (SCBA) and sugar cane straw ash (SCSA) were incorporated by replacing 10 to 25 wt.% of Portland cement in PC mixtures with aggregate to binder ratio of 3.5 to 5.0. The results demonstrated that mixtures with a smaller amount of cement (e.g. aggregate to binder 5.0), compressive strength was enhanced when compared to their respective control sample. Furthermore, the greatest compressive strength was achieved for 10 wt.% of both sugar cane wastes, reaching about 13.2 MPa for 10% SCBA and for 10% SCSA about 12 MPa. On the other hand, sand was used as fine aggregate replacing 15% to 59% of the cement paste, in PC mixtures with design porosities set at 25%, 30% and 35%. The results demonstrated that up to 38% of sand can be incorporated by replacing cement paste, without causing a reduction in hydraulic and mechanical properties and without significantly altering the porosity compared to control mixtures (100% Portland cement). This could represent savings of about 100 kg/m³ of cement compared with ordinary PC reported in the literature. Furthermore, life-cycle assessment demonstrated a reduction in environmental impact when sand replaced paste volume by up to about 38% while economic cost analysis predicted that cost savings in materials could be around 10-25%. Finally, the multi-criteria performance evaluation demonstrated that ideal paste volume replacement could be influencied by the size of coarse aggregate. Therefore, the well-planned partial replacement of Portland cement or cement paste could represent more functional, efficient and sustainable pervious concretes.

O concreto permeável (PC) é um material com macroporos interligados (aprox. 15-35% de porosidade) que permite o escoamento da água pela sua estrutura, geralmente utilizado em pavimentos permeáveis. É elaborado com agregados graúdos unidos por pasta cimentícia e geralmente com pouca ou nenhuma incorporação de agregado miúdo, o que garante porosidade interconectada. Devido à ausência de finos e à elevada porosidade, este material pode necessitar de maior quantidade de cimento e atingir desempenhos mecânicos inferiores aos do concreto convencional. Considerando as questões ambientais e de custos associadas à produção de cimento Portland, este trabalho focou na utilização de materiais cimentícios suplementares e agregados finos em substituição ao cimento Portland em concretos permeáveis. Cinza de bagaço de cana-de-açúcar (SCBA) e cinza de palha de cana-de-açúcar (SCSA) foram incorporadas substituindo 10 a 25% em peso de cimento Portland em misturas de PC com relação agregado/ligante de 3,5 a 5,0. Os resultados demonstraram que em misturas com menor quantidade de cimento (ex. agregado/ligante 5.0), a resistência à compressão foi melhorada quando comparada com a respectiva amostra controle. Além disso, a maior resistência à compressão foi alcançada para 10% em ambos os resíduos de cana-de-açúcar, atingindo cerca de 13,2 MPa para 10% SCBA e para 10% SCSA cerca de 12 MPa. Já a areia foi utilizada como agregado fino em substituição de 15% a 59% da pasta de cimento, em misturas de PC com porosidades de projeto fixadas em 25%, 30% e 35%. Os resultados demonstraram que até 38% de areia pode ser incorporada em substituição à pasta de cimento, sem causar redução nas propriedades hidráulicas e mecânicas e sem alterar significativamente a porosidade em comparação às misturas controle (100% cimento Portland). Isto poderia representar uma economia de cerca de 100 kg/m³ de cimento em comparação com o PC comum relatado na literatura. Além disso, uma avaliação do ciclo de vida demonstrou uma redução no impacto ambiental quando a areia substituiu volume de pasta em até 38%, enquanto a análise de custos econômicos previu que a redução de custos em materiais poderia ser de cerca de 10-25%. Finalmente, a avaliação de desempenho multicritério demonstrou que a substituição ideal do volume de pasta pode ser influenciada pelo tamanho do agregado graúdo. Portanto, a substituição parcial bem planejada do cimento Portland ou da pasta de cimento podem proporcionar concretos permeáveis mais funcionais, eficientes e sustentáveis.
Substituição de cimento em concreto permeável: viabilidade do uso de cinzas de cana-de-açúcar e areia considerando o desempenho global do material
Keywords: Pervious concrete; Sugar cane wastes; Fine aggregate; Cement replacement; Concreto permeável; Resíduos da cana-de-açucar; Agregado fino; Substituição de cimento